Does asymptomatic bacteriuria affect the response to intravesical bacillus Calmette–Guérin?. (29th October 2019) - Herr, Harry
Abstract : Objective: To determine the initial response to intravesical bacillus Calmette–Guérin and the 3‐year recurrence rate of high‐risk non‐muscle‐invasive bladder cancer in patients who have asymptomatic bacteriuria. Methods: Response and recurrence rates were investigated in 505 patients with high‐risk non‐muscle‐invasive bladder cancer after treatment with induction bacillus Calmette–Guérin (TICE strain) therapy. Initial response was determined after 3 months and patients were followed every 3–6 months for 3 years. Before bacillus Calmette–Guérin and each follow‐up cystoscopy, urine cultures were obtained, stratified as no growth, <104, >104 or >105 colony‐forming unit/mL. Any degree of bacteriuria on culture was classified as asymptomatic bacteriuria. Results: Of the 505 cases, 270 (53%) had asymptomatic bacteriuria. A total of 89% of patients with asymptomatic bacteriuria showed a complete response to bacillus Calmette–Guérin versus 76% of uninfected patients ( P = 0.001), and 75% of bacteriuric patients survived tumor‐free for 3 years versus 65% of uninfected patients. Conclusions: Chronic bacteriuria might enhance the response of high‐risk non‐muscle‐invasive bladder cancer to intravesical bacillus Calmette–Guérin and result in longer tumor‐free survival than uninfected patients.